Proces nabywania kompetencji obywatelskich przez uczniów w przestrzeni szkoły – analiza podstaw teoretycznych - Kamecka-Antczak, Celina (Kultura-Społeczeństwo-Edukacja, 2020)
The article analyses three selected theories: the theory of communicative action proposed by Jürgen Habermas, the theory of social learning by Albert Bandura, as well as dramaturgical theory by Erving Goffman. The aim of the analysis was to find one leading theory of the process of acquiring civic competences. The selected theory should meet the set conditions that allow it to be used in school space. Civic competences are understood as a particular subtype of social competences, the acquisition of which is an important element of social development. The scope of the definition of civic competences depends on the theoretical approach adopted. School space is a community made up of students, teachers and parents, who focus on a common goal. This space is also where students’ socialisation takes place. The analysis was carried out on the basis of 5 questions regarding the subject, determinants, mechanism, place in development, and criteria for verifying the process of acquiring civic competences by students in the school space. The answers to the questions listed in the table have become the criteria for the analysis. However, this analysis did not allow for choosing a leading theory. None of the theories has met all the conditions set.